2022
DOI: 10.1200/po.21.00446
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Tumor Regression With Zenocutuzumab, a Bispecific Antibody Targeting Human Epidermal Growth Factor Receptor 2/Human Epidermal Growth Factor Receptor 3 Signaling, in NRG1 Fusion–Positive, Estrogen Receptor–Positive Breast Cancer After Progression on a Cyclin-Dependent Kinase 4/6 Inhibitor

Abstract: Creative Commons Attribution Non-Commercial No Derivatives 4.0 License Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…72 The modified Bispecific antibodies targeting HER2 × CD3 (ertumaxomab), HER2 × CD16, and HER2 × HER3 (zenocutuzumab: MCLA-128 and MM-111) are being developed in addition to naive antibodies. [73][74][75][76][77][78] Recently, progress has been made in the creation of bispecific antibodies that target both the immune checkpoint molecules PD-1/ PD-L1 and HER2, with antitumor effects proven in preclinical animals. 79,80 In trastuzumab-resistant cancer models, bispecific antibodies targeting immune checkpoint molecules and HER2 may be more successful than individual mAb treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…72 The modified Bispecific antibodies targeting HER2 × CD3 (ertumaxomab), HER2 × CD16, and HER2 × HER3 (zenocutuzumab: MCLA-128 and MM-111) are being developed in addition to naive antibodies. [73][74][75][76][77][78] Recently, progress has been made in the creation of bispecific antibodies that target both the immune checkpoint molecules PD-1/ PD-L1 and HER2, with antitumor effects proven in preclinical animals. 79,80 In trastuzumab-resistant cancer models, bispecific antibodies targeting immune checkpoint molecules and HER2 may be more successful than individual mAb treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Bispecific antibodies targeting HER2 × CD3 (ertumaxomab), HER2 × CD16, and HER2 × HER3 (zenocutuzumab: MCLA‐128 and MM‐111) are being developed in addition to naive antibodies 73–78 . Recently, progress has been made in the creation of bispecific antibodies that target both the immune checkpoint molecules PD‐1/PD‐L1 and HER2, with antitumor effects proven in preclinical animals 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…Bispecific antibodies targeting HER2×CD3 (ertumaxomab), HER2×CD16, and HER2×HER3 (zenocutuzumab: MCLA-128 and MM-111) are being developed in addition to naive antibodies [69][70][71][72][73][74]. Recently, progress has been made in the creation of bispecific antibodies that target both the immune checkpoint molecules PD-1/PD-L1 and HER2, with antitumor effects proven in preclinical animals [75,76].…”
Section: Discussionmentioning
confidence: 99%
“… 53 In a clinical trial involving NRG1 fusion-positive/estrogen receptor-positive breast cancer patients who had experienced disease progression after treatment with cyclin-dependent kinase 4/6 inhibitors, zenocutuzumab demonstrated sustained tumor regression. 54 The I/II phase eNRGy clinical trial (NCT02912949) included patients with NRG1 fusions in three cohorts: NSCLC (25 cases), pancreatic cancer (13 cases), and other solid tumors (13 cases). The results of the study showed excellent efficacy of zenocutuzumab in pancreatic cancer patients, with a partial response observed in 42% (5/12) of patients, stable disease in 6 cases, and disease progression in only 1 case.…”
Section: Treatment Strategies For Nrg1/nrg2 Fusionmentioning
confidence: 99%